2023
DOI: 10.1061/(asce)st.1943-541x.0003473
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Efforts to Promote Steel Reuse in Building Construction

Abstract: This paper describes the state-of-the-art of structural steel reuse in Japan. A significant part of the material is taken from a document titled the AIJ Recommendations for Sustainable Steel Building Construction (Draft) available only in the Japanese language. The motivations and potential benefits of steel reuse are examined. The affinity between seismic design requirements and steel reuse is highlighted through a concept known as "damage-control" design. Some technologies for disassembly are introduced. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…This naturally results in a majority of Review publications, aligning with previous patterns, giving an even distribution between DfD and Reuse. The topics emphasized are LCA [21,57,[69][70][71], adaptability [21][22][23][24]57,69,70,72,73], and the potential of CE integration within specific materials like concrete [18,22,24,74], timber [23,75], and steel [73,[76][77][78][79][80], which is further explored in Section 4.5. Additionally, through the further examination of publications within the CE investigation, the recurrent critical research gaps have been identified as the need for precise standardization [21][22][23]57,74,77,78,81], digital tool integration [81], and overcoming challenges in policy [69,76,78], market acceptance [73,78], and industry-wide adoption to advance CE [18,22,72,74,…”
Section: Research Type and Circular Designmentioning
confidence: 99%
See 1 more Smart Citation
“…This naturally results in a majority of Review publications, aligning with previous patterns, giving an even distribution between DfD and Reuse. The topics emphasized are LCA [21,57,[69][70][71], adaptability [21][22][23][24]57,69,70,72,73], and the potential of CE integration within specific materials like concrete [18,22,24,74], timber [23,75], and steel [73,[76][77][78][79][80], which is further explored in Section 4.5. Additionally, through the further examination of publications within the CE investigation, the recurrent critical research gaps have been identified as the need for precise standardization [21][22][23]57,74,77,78,81], digital tool integration [81], and overcoming challenges in policy [69,76,78], market acceptance [73,78], and industry-wide adoption to advance CE [18,22,72,74,…”
Section: Research Type and Circular Designmentioning
confidence: 99%
“…SC: [67] Upcycling SC: [55,56] Reuse SC: [85,96], CE: [79] CD: [61][62][63][64][65][87][88][89][90][91][92]97] CT: [20,[30][31][32]34] CD: [62,84], CE: [18,70,[73][74][75][76]78,80] CE: [98] General CE CT: [68] CT: [16] CE: [57], CT: [58,59], CD: [60] DfD and Reuse SC: [35] DfD CT: [94,95,99], CE: [71], SC: [66,[100][101][102] CD: [83,…”
Section: Deconstructionmentioning
confidence: 99%
“…Construction industry is taking countless measures to reduce the carbon footprint as world is currently facing environmental and climate challenges. Literature has reported that one third of the CO 2 emissions are produced by the construction industry [1][2][3]. Production of structural steel requires quite lot of energy which emit approximately three billion tons of CO 2 each year [4].…”
Section: Introductionmentioning
confidence: 99%